Regional Aspirations and Limits of Power-Turkish-Iranian Relations in the New Middle East - Ayman, S. Gülden (Études helléniques / Hellenic Studies, 2012)
This article aims at highlighting the relationship between security problems and regional aspirations of Turkey and Iran with a special emphasis given to the accelerated competition between the two neighbors after the two developments: The US decision to withdraw from Iraq and the Arab Spring. The leading questions of the article are as follows: What are the fundamental factors that drive Iran and Turkey to lead the region? How both parties approach the current state of the Middle East? What type of power bases they have? What type of strategies have been adopted by both countries? What is the nature of their relations with the US? How regional and external actors aﬀect Turkish-Iranian competition? Analyzing the Turkish-Iranian case the article shows that one of the most important factors that motivate states to seek hegemony is the perceived security needs that are thought to be fulflled mainly through enhancement of power capabilities. It underlines the fact that what diﬀerentiates Turkish quest to lead the region from Iran’s aspirations is not the need of security but under what kind of conditions it is thought to be fulflled.